Is the hemispheric asymmetry of sunspot cycle caused by an irregular process with long-term memory?. Issue 1 (13th January 2022) - Das, Ratul; Ghosh, Aparup; Karak, Bidya Binay
ABSTRACT: The hemispheric asymmetry of the sunspot cycle is a real feature of the Sun. However, its origin is still not well understood. Here, we perform nonlinear time series analysis of the sunspot area and number asymmetry to explore its dynamics. By measuring the correlation dimension of the sunspot asymmetry, we conclude that there is no strange attractor in the data. Further computing Higuchi's dimension, we conclude that the hemispheric asymmetry is largely governed by stochastic noise. However, the behaviour of Hurst exponent reveals that the time series is not completely determined by a memory-less stochastic noise, rather there is a long-term persistence, which can go beyond two solar cycles. Therefore, our study suggests that the hemispheric asymmetry of the sunspot cycle is predominantly originated due to some irregular process in the solar dynamo. The long-term persistence in the solar cycle asymmetry suggests that the solar magnetic field has some memory in the convection zone.